Impact of communication and the media on ethnic conflict - Gibson, Steven 1955-; Lando, Agnes Lucy (Advances in media, entertainment, and the arts (AMEA) book series, 2016)
Focuses on both the positive and negative outcomes of communication and media usage, as well as the overall perceptions of these elements, within conflicting populations. This volume features theoretical perspectives on various intergroup interaction experiences within contemporary ethnic controversies